Advancing knowledge about developmental and life-course criminology. Issue 3 (September 2015) - McGee, Tara Renae; Farrington, David P; Homel, Ross; Piquero, Alex R
Developmental and life-course criminology is concerned mainly with three topics: (1) the development of offending and antisocial behavior from childhood to adulthood; (2) risk and protective factors for offending and antisocial behavior; and (3) the effect of life events on the course of development. The main aim is to study changes within individuals over time in risk factors and life events, and to relate them to later changes in offending. This special issue of the Australian and New Zealand Journal of Criminology brings together a range of papers focused around this aim.